Internet of Things in Greenhouse Cultivation of Chrysanthemum Flowers in Primadona Tomohon Farmers Group - Milytia Christabella Tumengkol; Kofal Hilkiah Lasewa; Jarot S Suroso (Politeknik Pertanian Negeri Samarinda, 2025)
The application of the Internet of Things (IoT) in greenhouses provides innovative solutions to enhance the efficiency and quality of chrysanthemum cultivation for the Primadona farmer’s group in Tomohon. The application of the automated system created is a condensation system that activates when the average temperature inside the greenhouse reaches 28 °C during the vegetative phase and 23°C during the generative phase, a drip irrigation system that turns on automatically when the average soil moisture value reaches 50%, as well as UV lights and exhaust fans that operate at night. The application of IoT also enables farmers to monitor and control greenhouse climate conditions in real-time using the Blynk application. The research method employed is experimental, incorporating a literature study to understand the application of IoT in greenhouses for chrysanthemum cultivation, as well as analysis of hardware and software requirements, system design, and system testing for real-world operations. The evaluation of the results provides insights into the effectiveness of IoT implementation in greenhouses for chrysanthemum cultivation, particularly for the Primadona Tomohon farmer group.